Severe Acute Respiratory Syndrome Coronavirus 2: Vaccine Hesitancy Among Underrepresented Racial and Ethnic Groups With HIV in Miami, Florida. (26th March 2021) - Jones, Deborah L; Salazar, Ana S; Rodriguez, Violeta J; Balise, Raymond R; Starita, Claudia Uribe; Morgan, Kristiana; Raccamarich, Patricia D; Montgomerie, Emily; Nogueira, Nicholas Fonseca; Barreto Ojeda, Irma; Maddalon, Marissa; Rodriguez, Nicolle L Yanes; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and human immunodeficiency virus (HIV) disproportionally affect underrepresented ethnoracial groups in the United States. Medical mistrust and vaccine hesitancy will likely impact acceptability of SARS-CoV-2 vaccines. This study examined SARS-CoV-2 vaccine hesitancy among underrepresented ethnoracial groups with HIV and identified factors that may reduce vaccine uptake. Methods: We conducted a cross-sectional study of adults ≥18 years of age with HIV residing in Miami, Florida. Participants were invited to participate in the ACTION (A Comprehensive Translational Initiative on Novel Coronavirus) cohort study. A baseline survey was administered from April to August 2020 and followed by a coronavirus disease 2019 (COVID-19) vaccine hesitancy survey from August to November 2020. The COVID-19 vaccine hesitancy survey was adapted from the Strategic Advisory Group of Experts survey. Comparisons by race and ethnicity were performed using the Freedman-Haltmann extension of the Fisher exact test. Results: A total of 94 participants were enrolled; mean age was 54.4 years, 52% were female, 60% were Black non-Latinx, and 40% were non-Black Latinx. Black non-Latinx participants were less likely to agree that vaccinations are important for health when compared to non-Black Latinx (67.8% vs 92.1%, P = .009), less likely to agree that vaccines are effective in preventing disease (67.8% vs 84.2%, P = .029), less likely to believe that vaccine information is reliable and trustworthy (35.7% vs 71.1%, P = .002), and less likely to believe vaccines were unnecessary because COVID-19 would disappear soon (11% vs 21%, P = .049). Conclusions: Medical mistrust, vaccine hesitancy, and negative sentiments about SARS-CoV-2 vaccines are prevalent among underrepresented ethnoracial groups with HIV, particularly Black non-Latinx. Targeted strategies to increase vaccine uptake in this population are warranted.